Legal Mechanism: Foreign Brand Claims Against Potentially Geographical Indications of Indonesia - Dara Quthni Effida Dara; Putri Kemala Sari Putri; Eza Aulia Eza; Asmaul Husna Nana (Jurnal Hukum Samudra Keadilan, 2022)
International community has recognized the superiority and quality of original Indonesian products, as a result, some native Indonesian products are claimed by foreigners as their trademarks, for example Gayo Arabica Coffee and Toraja Coffee. Indonesia in providing protection is a bit behind in seeing the potential of its own region. The research problem is to examine the juridical claims of foreign companies against products with potential Indonesian Geographical Indications, and the settlement mechanism based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Research method used is normative juridical with a statute approach. Claim of foreign companies against products with the potential for Indonesian Geographical Indications is the use of Intellectual Property Rights without rights, based on the MUI Fatwa decision, this is an injustice that is unlawful. The legal settlement mechanism for foreign brand claims against products with potential Indonesian Geographical Indications based on Law Number 20 of 2016 concerning Marks and Geographical Indications is dependent on the violation of the claim, whether the party making the claim is in good faith or not. If at the time a sign is applied for registration as a Geographical Indication, a sign is used in good faith, the party can still use it for a period of two years, but if there is no good faith, it can take the mechanism of filing a lawsuit in the form of an application for compensation against the User of the Geographical Indication without rights.